145k views
0 votes
Simplify the expression below by rationalizing the denominator. When typing your answer be sure to be careful and include the correct signs. Keep in mind that the variables a,b,c,d, e and f can represent a product of a number and a variable. \frac{\sqrt[]{8}}{1-\sqrt[]{3z}} simplifies to \frac{a\sqrt[]{b}+c\sqrt[]{d}}{e- \sqrt[]{f}} Our value for a is AnswerOur value for b is AnswerOur value for c is AnswerOur value for d is AnswerOur value for e is AnswerOur value for f is Answer

Simplify the expression below by rationalizing the denominator. When typing your answer-example-1

1 Answer

4 votes

Given:


\frac{\sqrt[]{8}}{1-\sqrt[]{3z}}

Simplife:


\begin{gathered} =\frac{\sqrt[]{8}}{1-\sqrt[]{3z}} \\ =\frac{\sqrt[]{8}}{1-\sqrt[]{3z}}*\frac{1+\sqrt[]{3z}}{1+\sqrt[]{3z}} \\ =\frac{\sqrt[]{8}+\sqrt[]{24z}}{1-\sqrt[]{9z^2}} \\ =\frac{2\sqrt[]{2}+2\sqrt[]{6z}}{1-\sqrt[]{9z^2}} \end{gathered}

The given simplifies equation is:


\frac{a\sqrt[]{b}+c\sqrt[]{d}}{e-\sqrt[]{f}}

After the compare the both inequality:

a=2

b=2

c=2

d=6

e=1

f=9

User Claude
by
5.5k points